Advancing student well-being and agency: the outline of a ‘capabilities-friendly’ approach - Walker, Melanie (South African Journal of Higher Education, 2016)
The article outlines the case for the capabilities-friendly approach in higher education practice, policy and evaluation. According to this normative approach to human well-being and agency, higher education ought to enable the full range of opportunities and achievements for every students, and for diverse students, while also contributing to commitments to the good of others. As such it is an inclusive, social justice friendly approach, concerned with equity in higher education and reducing inequalities in society through the actions of graduates. By drawing on a theoretical approach in the development ethics field rather than only from the higher education literature, the article further seeks to align development with higher education in ways which might benefit both fields. To illustrate the argument for capabilities, the article details the lives of two students and then uses the examples to sketch different approaches to information on and the evaluation of well-being, with the capability approach argued for as the most robust. The article then details the need also for the educational formation of agents who will make ethical contributions to reducing inequalities and poverty in society. Three worthwhile higher education capabilities are advanced: affiliation, critical capacities and ethical citizenship. Finally, some of the gaps in the capability approach are noted.